Left of poetry Depression America and the formation of modern poetics - Ehlers, Sarah (University of North Carolina Press, 2019)
"In this incisive study, Sarah Ehlers returns to the Depression-era United States in order to unsettle longstanding ideas about poetry and emerging approaches to poetics. By bringing to light a range of archival materials and theories about poetry that emerged on the 1930s left, Ehlers reimagines the historical formation of modern poetics. Offering new and challenging readings of prominent figures such as Langston Hughes and Muriel Rukeyser, and uncovering the contributions of lesser-known writers such as Jacques Roumain, Genevieve Taggard, and Martha Millet, Ehlers illuminates an aesthetically and geographically diverse matrix of schools and movements"...